Domain and method-specificity of acquiescence estimated in different measures. (March 2022) - Havan, Patrik; Kohút, Michal; Halama, Peter
Abstract: Acquiescence is a tendency to systematically agree with all items without regard to their content. It is questionable whether acquiescence is consistent across different domains and methods (e.g. Danner & Rammstedt, 2016). The goal of this study was to investigate the possible consistency or specificity of domains and methods. The sample consists of 414 participants. We used four measures for estimating acquiescence: one personality inventory (Big Five Inventory 2), two attitude scales (authoritarian/anti-immigrant attitude scale and attitudes towards refugees scale), and one knowledge test (coronavirus knowledge test). Acquiescence was estimated using the latent approach with CFA (e.g. Billiet & McClendon, 2000). We estimated acquiescence in all domains and methods except the coronavirus knowledge test and found that acquiescence is method-consistent. Because of the consistency of acquiescence across different domains and methods, we consider acquiescence rather participant-related. The inability of estimating acquiescence could be caused by beliefs in conspiracy theories interfering with coronavirus knowledge test or by differential functioning of acquiescence in knowledge tests.